Aetiology and Treatment Outcome of Non-traumatic Small Bowel Perforations at Mbarara Hospital in South-Western Uganda - Mutiibwa, D.; Lopez, A.; Tumusiime, G.; Riding, D.; Diaz, A. (COSECSA/ASEA Publication, 2012)
Non-traumatic small bowel perforation (SBP) is the most common form of gastrointestinal perforation in sub-Saharan Africa. Although SBP is a surgical emergency associated with complications, information regarding its aetiology is scanty in Uganda. This study was aimed at determining the aetiology and document treatment outcomes of non-traumatic small bowel perforations in South-western Uganda.
Keywords: Treatment Outcome; Non-traumatic; Small Bowel Perforations; Mbarara Hospital; Aetiology